EKSPLORASI ETNOMATEMATIKA PADA AKTIVITAS PETANI BAWANG MERAH DI DESA BANYUANYAR KABUPATEN PROBOLINGGO - Abdur Rofiq; Nuryami (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2024)
Mathematics has an important role in solving problems in everyday life. Mathematics continues to develop periodically following the difficulties encountered from various cultural backgrounds. Ethnomathematics has the aim of connecting mathematics with culture, ethnomathematics can be a link between mathematics that has been learned at school and mathematics that exists outside of school, therefore researchers are interested in observing shallot farmers to get information related to mathematical concepts used in every activity on their farm. Qualitative research through an ethnographic approach is suitable for this research because researchers seek information directly based on the description and analysis of culture in the community. The results of the research found many mathematical concepts in the activities of farmers in Banyuanyar village such as the concepts of addition, multiplication, profit sharing system, fraction multiplication, worth comparison, block area and others. With this research, hopefully it can help teachers in explaining to students about mathematics with real examples in the surrounding environment, and for further researchers it can be a reference and explore more mathematical concepts around through existing cultural culture.Keywords: ethnomathematics; farmers; shallots